Nitrite amperometric sensor for gunshot residue screening. (20th January 2020) - Promsuwan, Kiattisak; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Abstract: A novel electrochemical sensor comprising a glassy carbon electrode modified with a composite of palladium (Pd) particles and glassy carbon microspheres (GCMs), has been developed to detect gunshot residue via nitrite determination. Pd-GCMs was synthesized through a simple electroless deposition method and characterized by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The electrocatalytic response of nitrite on the Pd-GCMs/GCE is greatly enhanced relative to that on a GCMs/GCE and bare GCE. The applied potential, flow rate and sample volume of flow injection amperometric detection were optimized. The sensor displayed a linear response to nitrite between 0.10 μmol L −1 and 4.0 mmol L −1, with a limit of detection and quantification of 0.030 and 0.11 μmol L −1, respectively. It exhibited very good performance with excellent electrocatalytic activity and high sensitivity (500 ± 5 μA mM −1 cm −2 ). In addition, the electrochemical sensor presented good repeatability (RSD < 1.5%, n = 20), reproducibility (RSD = 1.4%, n = 6), and operational stability (RSD = 2.8%, n = 268), along with high sample throughput (165 samples h −1 ). The results of detecting nitrite in gunshot residue with this sensor were in good agreement with those obtained by the Griess method ( P>0.05 ). With its good performance this sensor could be a viable alternative method for detecting nitrite to identify gunshot residue in forensic evaluations via nitrite detection. Graphical abstract: Image 1 Highlights: Novel nitrite amperometric sensor for gunshot residue screening. Pd-GCMs/GCE exhibited excellent electrocatalytic nitrite oxidation performance. FI amperometric nitrite sensor shows high sensitivity, low LOD and wide linear range. High-throughput screening (165 samples per hour). This sensor successfully detected nitrite in gunshot residue.